2021
DOI: 10.1038/s41421-021-00270-5
|View full text |Cite
|
Sign up to set email alerts
|

Phase separation of EML4–ALK in firing downstream signaling and promoting lung tumorigenesis

Abstract: EML4–ALK fusion, observed in about 3%–7% of human lung adenocarcinoma, is one of the most important oncogenic drivers in initiating lung tumorigenesis. However, it still remains largely unknown about how EML4–ALK fusion exactly fires downstream signaling and drives lung cancer formation. We here find that EML4–ALK variant 1 (exon 1–13 of EML4 fused to exon 20–29 of ALK) forms condensates via phase separation in the cytoplasm of various human cancer cell lines. Using two genetically engineered mouse models (GEM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
42
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 33 publications
4
42
2
Order By: Relevance
“…This is consistent with the key structural difference between EML4‐ALK V1 and V3—the longer variant includes the incomplete globular TAPE domain of EML4 that is predicted to aggregate due to exposure of its hydrophobic core and which confers dependence on the chaperone Hsp90 for stability (Richards et al , 2014 ). As the existence of LLPS foci, such as FUS, which are formed by phase separation, is implicated in neurodegenerative diseases, the presence of similar compartments in cancers, such as EML4‐ALK + NSCLC, could also contribute to the progression and aggressiveness of the disease (Qin et al, 2021 ). Therefore, we suggest that disruption of the foci using specific compounds which alter phase behaviour or inhibitors of key protein–protein interactions might provide an additional route to targeting EML4‐ALK V3, as part of a concerted strategy to improve the outcomes of these higher‐risk patients.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with the key structural difference between EML4‐ALK V1 and V3—the longer variant includes the incomplete globular TAPE domain of EML4 that is predicted to aggregate due to exposure of its hydrophobic core and which confers dependence on the chaperone Hsp90 for stability (Richards et al , 2014 ). As the existence of LLPS foci, such as FUS, which are formed by phase separation, is implicated in neurodegenerative diseases, the presence of similar compartments in cancers, such as EML4‐ALK + NSCLC, could also contribute to the progression and aggressiveness of the disease (Qin et al, 2021 ). Therefore, we suggest that disruption of the foci using specific compounds which alter phase behaviour or inhibitors of key protein–protein interactions might provide an additional route to targeting EML4‐ALK V3, as part of a concerted strategy to improve the outcomes of these higher‐risk patients.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it promotes the establishment of super-enhancer, thereby activating leukaemogenic genes. Similarly, in lung cancer, Qin et al [ 289 ] reported EML4-ALK fusion aggregates through phase separation in various cancer cell lines. This fusion protein activates downstream STAT3-mediated signalling pathways, thereby promoting tumorigenesis.…”
Section: Key Structural Elements Mediating 3d Chromatin Interactionsmentioning
confidence: 99%
“…Currently the most common EML4-ALK fusion genotypes in NSCLC are as follows: EML4-ALK V1 (exon 13 of EML4 fused to exon 20 of ALK; 33%), EML4-ALK V2 (exon 20 of EML4 fused to exon 20 of ALK; 10%), EML4-ALK V3 a/b (exon 6 of EML4 is fused to exon 20 of ALK; 29%) (Fig. 2) (41)(42)(43), and different fusion genotypes have different tyrosine kinase activities (44). Further research on the differences in biological behavior among variants of the EML4-ALK fusion gene is required (45).…”
Section: Eml4-alk Fusion Genementioning
confidence: 99%